UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATERI GELOMBANG ELEKTROMAGNETIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DI KELAS XI MIPA-3 SMA NEGERI 2 MUTIARA - Marni Marni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This study aims to determine the increase in learning abilities of students in class XI MIPA-3 physics lessons on electromagnetic waves for the 2020/2021 school year through the Numbered Head Together (NHT) learning model. This research was conducted at XI MIPA-3 SMA Negeri 2 Mutiara, Pidie Regency, the research lasted for three months, from January to March 2021. The type of research used was classroom action research (PTK) which consisted of over 2 cycles. The subjects of the study were students of class XI MIPA-3 SMA Negeri 2 Mutiara, Pidie Regency, for the 2020/2021 academic year, which were 32 students. Data analysis used a comparative descriptive analysis technique by comparing the pre-cycle with the results achieved in each cycle, cycle I and cycle II. The percentage of completeness obtained in the first cycle was 68.8% with an average grade of71.9 and increased in the second cycle to 90.6% with an average grade of 78.6. In these two cycles there was a significant change in activity and score when compared to the pre-cycle with learning completeness which only reached 53.1% and the average score was 66.6. Thus, through the application of the Numbered Heads Together (NHT) learning model, it can improve learning outcomes on electromagnetic wave material in class XI MIPA-3 students of SMA Negeri 2 Mutiara, Pidie district.Keywords : Student Learning Outcomes, Electromagnetic waves, Numbered Head Together (NHT) learning model.